PENGARUH KEMATANGAN KARYAWAN DENGAN GAYA KEPEMIMPINAN SITUASIONAL PENGUSAHA PEREMPUAN SEBAGAI VARIABEL MODERATING TERHADAP KINERJA KARYAWAN - Ediningsih, Sri Isworo; Wisnalmawati, Wisnalmawati (Universitas Muhammadiyah Magelang, 2009)
The purpose of this study to analyze the influence of employees maturity on employees performance and that to investigate the influence employees maturity which is moderated by situational leadership style on employees performance. In this study using sample of several member's of IWAPI DIY. Data collected by questioner and the analysis technique by moderating regression analysis. The result of this study is employees maturity has significant influence on employees performance and situational leadership style didn't moderated correlation between employees maturity with employees performance.